Polska polityka azylowa. Ujęcie prawno-instytucjonalne - Potyrała, Anna (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
Polish refugee policy dates back to September 26, 1991 when the Republic of Poland ratified the Geneva Convention relating to the Status of Refugees of 1951 and the New York Additional Protocol of 1967. The adoption of provisions of both these international documents obliged Poland to amend the Law on Foreigners of March 29, 1963. The changes introduced in 1991 have not concluded the matter. Membership of the European Union resulted in the adaptation of Polish legislation to the requirements of the Common European Asylum System. Consequently, persons seeking asylum in Poland can be granted protection in the form of refugee status, temporary protection, asylum (defined as territorial asylum), subsidiary protection and tolerated residence. The dynamics of the European asylum law results from diversified migration situations in the member states, as well as from the necessity to guarantee the security of the EU and to work out a unified approach to asylum problems. All this requires further legal and institutional changes.